Who Has Trouble Hiring? Evidence from a National IT Survey. (May 2022) - Weaver, Andrew
Understanding hiring difficulties and the nature of hiring frictions that employers face is important for the promotion of economic growth and the individual success of both firms and workers. This study sheds light on this issue by presenting evidence from an original, nationally representative survey of information technology (IT) helpdesks that contains detailed measurements of skill requirements, organizational characteristics, and market structure. The results indicate that the incidence of persistent hiring difficulties is modest, and that measures of technology and technical skill demands are not associated with greater hiring problems. Organizational attributes and market structure are generally more predictive of hiring frictions than are skill requirements. Human resource practices, management strategy, and labor-market monopsony power all play key roles. These results cast doubt on simple stories about technology-driven hiring problems and point to the importance of examining a broader range of organizational and market factors when addressing workforce challenges.